2016
DOI: 10.1038/ncomms13955
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: N-type organic electrochemical transistors with stability in water

Abstract: Typographical errors were inadvertently introduced into the unit of charge mobility during the production process, such that the correct unit cm 2 V À 1 s À 1 was incorrectly give as cm À 2 V À 1 s À 1 . These errors do not affect the analysis of the results presented in the Article.The penultimate sentence of the second paragraph of the Article should read 'Recently, the electron mobility of n-type polymers has increased rapidly, reaching values of more than 1.0 cm 2 V À 1 s À 1 in OFETs, 12-17 thus enabling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…To further confirm the enhanced conductivity of dry crystalline P3MEEMT, we fabricated and tested organic field effect transistors (OFETs) and found a higher mobility in the annealed sample (Figure S21). Although initially counterintuitive, this difference in OFET mobility and OECT mobility is similar to findings by Giovannitti et al in which the polymer with greater dry field effect mobility and nearly equivalent volumetric capacitance performed significantly worse as an OECT . Both of these experiments suggest that changes in the polymer in its hydrated or doped state can have a detrimental effect on electronic transport.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…To further confirm the enhanced conductivity of dry crystalline P3MEEMT, we fabricated and tested organic field effect transistors (OFETs) and found a higher mobility in the annealed sample (Figure S21). Although initially counterintuitive, this difference in OFET mobility and OECT mobility is similar to findings by Giovannitti et al in which the polymer with greater dry field effect mobility and nearly equivalent volumetric capacitance performed significantly worse as an OECT . Both of these experiments suggest that changes in the polymer in its hydrated or doped state can have a detrimental effect on electronic transport.…”
Section: Resultsmentioning
confidence: 79%
“…OECT performance enhancement using oligoethylene glycol side chains is generalizable to a number of different conjugated backbones, including polythiophene, benzodithiophene, propylene­dioxythiophenes, and bi­thio­phene–thieno­thiophene . Additionally, ethylene glycol side chains have been shown to increase the OECT performance compared to that of their alkyl analogues in n-type polymers based on naphthalene tetracarboxylic diimide. , In each of these instances, the presence of ethylene glycol side chains improves both the steady-state characteristics (transconductance) and the switching kinetics of OECTs. Well-designed polymers now function as single-phase, accumulation-mode OECTs with volumetric capacitances approaching the theoretical limit of approximately 400 F cm –3 in aqueous environments. , …”
Section: Introductionmentioning
confidence: 99%
“…Initial work in the mixed conductor field showed that increased swelling in the presence of electrolyte leads to higher ionic conductivity. Thus, the design of modern organic mixed conductors is largely based upon substituting hydrophilic side chains, which promote hydration and ion transport, onto polymer backbones and small molecules known to have high electronic conductivity. This strategy has proven very successful, as polymers with polar side chains, including alcohols, carboxylic acids, amides, sulfonates, and most commonly, oligoethylene glycol, display dramatically enhanced ion transporting properties while maintaining their good electronic properties.…”
mentioning
confidence: 99%
“…The monomers TDPP(BE) 2 , 3ETGTDPP-Br 2 , BBT(SnBu 3 ) 2 , and NDITEG-Br 2 were synthesized by following procedures reported in the literature. 48,51,52 Methods. Average molecular weights (M w , M n ) were determined by gel permeation chromatography (GPC) against polystyrene standards.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The required four monomers 3TEGTDPP-Br 2 , BBT(SnBu 3 ) 2 , TDPP(BE) 2 and NDITEG-Br 2 were synthesized according to the literature reported procedures. 51,52 The polymer BBT-3TEG-TDPP was obtained with Stille coupling of BBT (SnBu 3 ) 2 and TDPP-3TEG-TDPP by using Pd(PPh 3 ) 4 as a catalyst, whereas polymers TDPP-3TEG-TDPP and P(gNDI-TDPP) were synthesized via Suzuki coupling reaction by using Pd 2 (dba) 3 as the catalyst. The detailed procedures for the synthesis of polymers are described in the Supporting Information.…”
Section: ■ Introductionmentioning
confidence: 99%